Hole-filling Algorithm for High-curvature Region in Triangular Mesh Models - Liu Xumin; Li Cailing; Wang Xiaojun (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
As the problem of hole-filling in the high-curvature region of the triangular mesh isn’t satisfactory, a new algorithm is proposed. In the mesh subdivision process, judge the mean curvature of the triangles that have a common edge, if the edge in the high curvature area, inserting new vertices in different ways according to the different situations of the edge length to achieve the mesh subdivision. The algorithm can make holes with neighboring mesh transit more natural and the repairing effect is satisfactory by many examples. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1549